Latent learning in the work place: the placement experiences of student-coaches. Issue 1 (2nd January 2018) - Gomes, Rúben; Jones, Robyn L.; Batista, Paula; Mesquita, Isabel
ABSTRACT: The aim of this study was to investigate the work-based internship experiences of eight student-coaches. This was particularly in terms of what precisely such coaches learned within the practical context, and how they engaged with unexpected situational events. The methods employed within the project included focus group interviews and participant observation. In particular, the student-coaches were both interviewed and observed over the course of a nine-month sporting season, with each phase of the research informing the next. The subsequent data were primarily subject to a thematic analysis. The findings of the study were organized under four principal themes: (1) the reality shock felt by the student-coaches in terms of the gap between what they expected and what they experienced; (2) the lack of respect demonstrated by the organizational head coaches for the students; (3) the students' response in terms of developing their micro-political literacy; and (4) the social price paid by the student-coaches in adopting such action. The results point to the limitations of student learning within high-performance sporting environments. In this respect, the student-coaches' experiences were not what was expected or desired. Despite this, many valuable and relevant lessons were learned. These related to developing students' micro-political literacy; necessary knowledge for any neophyte coaches trying to establish bone-fide situational roles.